Evaluation of growth, yield and some quality characteristics of sweet corn under effect of different nutrient sources - Mohammed, Aram Abbas; Majid, Zana M.; Kasnazany, Sidiq Aziz Sidiq; Rashis, Zanko Othman; Hama, Bexal Mustafa (Sulaimani Journal for Pure and Applied Sciences, 2018)
In order to investigate the effect of organic and chemical nutrients on the growth and yield and yield quality of two varieties of sweet corn, two different field experiments were conducted in spring and autumn seasons in 2017, the experimental design was laid out as a split-plot design with three replications. Two sweet corn varieties Goldrash and Chocleta putted in the main plots while three different nutrient sources were fixed in sub-plots. Several vegetative and reproductive growth criteria were studied as well as the rate of accumulated dry matter that allocated to the leaves and stem in two different growth stages pre and post silking were measured. The quality related criteria M%, TS, TSS, and NSS was evaluated. Results of both seasons demonstrated the effectively of organic nutrient sources in exceeding chemical fertilization in a number of criteria or approaching its level in another, The interaction between second organic nutrient and Goldrash showed a maximum yield in the spring season, while the yield in autumn season was non significantly resulted.
Keywords: sweet corn; organic and chemical nutrients; seasons; qualitycharacteristics